Electrodeposited palladium on MWCNTs as 'semi-soluble heterogeneous' catalyst for cross-coupling reactions. Issue 27 (1st July 2015) - Radtke, Mariusz; Stumpf, Steffi; Schröter, Bernd; Höppener, Stephanie; Schubert, Ulrich Sigmar; Ignaszak, Anna
Graphical abstract